Process Supply Chains Management – Where are We? Where to Go Next? - Barbosa-Póvoa, Ana Paula (Frontiers in Energy Research, 2014)
Commonly Process Industries Supply Chains deal with chemical process based networks involving suppliers, producers, warehouses, retailers and distributors. More recently reverse logistics activities started to be also considered as part of such networks, being these responsible for incorporating into the forward chains non-conforming/ end of life products through recovering processes. This supports the exploration of the waste to value concept within the supply chains while addressing important environmental issues. The result of such behavior has increased the already complex management of such systems challenging the development of decision supporting tools that can help the related decision process. In this paper we address this need and analyse the more relevant published works that contribute to this goal while identifying the classes of problems that have been solved and which are the new trends in the area. We finalize this article by drawing some conclusions where we discuss advances performed and recognized challenges for the future.